2020
DOI: 10.31674/mjmr.2020.v04i03.002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Large Size and Multiple Benign Breast Lesions Using Oncoplastic Surgical Skills

Abstract: Objective: Management of multiple and large size benign breast lesions is challenging. Usual excision techniques are associated with unacceptable breast deformity in such cases. However, these can effectively be managed with minimum breast deformity using oncoplastic skills used for breast cancer. Our objective was to evaluate the oncological outcome and patient satisfaction of managing large and multiple benign breast lesions using oncoplastic surgical skills. Methods: This was a descriptive, prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…8 However, in a descriptive, prospective study conducted by Saleem et al Females with age range of 12 to 60 years were included, most of the patients were young with a mean age of 32.5 (SD=3.5) and BMI of 23.2 (SD= 1.4). 10 Also, we found that according to Breast masses there were 47 (94%) with breast mases with mean size of 4.61 (±2.42 SD), there were 4 (8%) with multiple lesions and 6 (12%) with bilateral disease, there were 20 (40%) with abscess, 13 (26%) with rubefaction, 16 (32%) with nipple retraction, 7 (14%) with skin ulceration and 12 (24%) with ductal fistulae with mean duration of symptoms of 9.04 (±8.78 SD) and range (1-44) months. In the study of Zhang et al 7 a periareolar mass was the most frequent symptom.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, in a descriptive, prospective study conducted by Saleem et al Females with age range of 12 to 60 years were included, most of the patients were young with a mean age of 32.5 (SD=3.5) and BMI of 23.2 (SD= 1.4). 10 Also, we found that according to Breast masses there were 47 (94%) with breast mases with mean size of 4.61 (±2.42 SD), there were 4 (8%) with multiple lesions and 6 (12%) with bilateral disease, there were 20 (40%) with abscess, 13 (26%) with rubefaction, 16 (32%) with nipple retraction, 7 (14%) with skin ulceration and 12 (24%) with ductal fistulae with mean duration of symptoms of 9.04 (±8.78 SD) and range (1-44) months. In the study of Zhang et al 7 a periareolar mass was the most frequent symptom.…”
Section: Discussionmentioning
confidence: 99%